Governança corporativa, estrutura de capital, rating soberano e desempenho da firma: uma análise em níveis multipaís, nacional e regional - Jesuka, Duterval (2020)
Firm theory studies show that managers have to deal with agency and information asymmetry problems to align their interests with those of shareholders, creditors and stakeholders, while keeping the company valued. Considering the influences of internal and external environments, this study aimed to analyze the relationship between corporate governance, capital structure, sovereign rating and firm performance at multi-country, national and regional levels. In a first step, a multilevel regression model was performed using a sample of 823 Latin American listed companies from 2004 to 2018. In a second step, data from 671 Brazilian listed companies and Brazil's sovereign rating between 2010 and 2017 were considered to analyze the performance behavior at the national and regional levels, more specifically in the Triangulo Mineiro and Alto Paranaíba and southern of Goiás regions. A panel data regression was employed. The results from the first study show that sovereign rating positively impact the capital structure and the performance of Latin American companies. The board size as well as the dual roles of the CEO / Chairman of the board can destroy firm’s value, while having an independent audit committee can increase both their indebtedness and performance. The evidence found reinforced the agency theory signaling that even with the adoption of good corporate governance practices, the more indebted companies are, the less valued they are. In the second study, at the national level we found that the board size, the audit reputation and sovereign rating positively affects the leverage of Brazilian companies. Return on assets was negatively influenced by the dual roles of the CEO / Chairman of the board and the size of the board, the return on equity is positively affected by the reputation of the audit, the concentration of ownership and control and the duality of CEO / Chairman. At the regional level, it was observed that companies that operate in TMAP and South Goiás regions are more leveraged due to the reputation of the audit and when there is an outsider in the board of directors, in contrast, leverage decreases when the board of directors is large and when there is concentration of ownership and control. Regarding to the performance, it was noted that for these companies ROA is positively influenced by the reputation of the audit and the presence of outsiders on the board, while the dual roles of CEO and Chairman can destroy it. Return on equity increases when there are professional directors on the board of directors, and decreases when there is a concentration of ownership and control.